FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENGOBATAN PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS PUDAKPAYUNG KOTA SEMARANG TAHUN 2019 - Siti Ihwatun; Praba Ginandjar; Lintang Dian Saraswati; Ari Udiyono (Jurnal Kesehatan Masyarakat (Undip), 2020)
Treatment adherence is one of the keys to the success of hypertension treatment, but medication adherence is still low in various regions. The purpose of this study was to analyze the relationship of duration of hypertension, duration of hypertension treatment, level of knowledge, medication motivation, perceptions of health services, and family support. The population of this study was hypertension sufferers who lived in the work area and examined themselves at the Pudakpayung Health Center, Semarang City, totaling 687 people. Sampling uses simple random sampling technique, so that the total sample obtained was 128 respondents. Variables were measured using a questionnaire. The results showed that factors significantly related to medication adherence were level of knowledge (p = 0,000 ; r = 0.839), treatment motivation (p = 0,000; r = 0.783), perception of health care (p = 0,000; r = 0.765), and family support (p = 0,000; r = 0.454). Duration of illness and duration of treatment did not have a significant relationship with hypertension treatment adherence.